CHARACTERIZATION OF PRUFER MODULE THROUGH PROPERTIES OF JOIN QUASI - TSUROIYAH, HANIF
Let R be a commutative ring with non-zero identity. A commutative ring with cancellation was known as an integral domain. The Prufer domain is an integral domain with specific property. The concept of a Prufer is related to a finitely generated invertible ideal. This thesis deals with the characterization of a Prufer domain through the properties of a join quasi cyclic submodule. Let M be non-zero R-module and faithful multiplication finitely generated. The necessary and sufficient conditions of a Prufer domain is for every finitely generated submodule of M is join quasi cyclic. It is know that the notion in Ring Theory can be adopted to Module Theory. As well as the notion of prufer. It is also shown that the necessary and sufficient conditions of a Prufer module M is for every finitely generated submodule otf M is join quasi cyclic.